Nearby Neighbourhood Influences on Adolescent Offending - Vogel, Matt (The British journal of criminology, 2021)
This study extends recent research on the spatial dynamics of neighbourhood disadvantage and youth offending. Data include self-reported offences from 794 Dutch adolescents and the socio-economic status in their residential neighbourhood and the surrounding community. The findings reveal that youth engage in the highest levels of offending when they reside in disadvantaged neighbourhoods surrounded by neighbourhoods characterized by relative affluence. This spatial pattern is attributable to greater temptations to offend, reduced parental monitoring, and more frequent involvement in unstructured activities among youths who live in close proximity to neighbourhoods more affluent than their own. This study highlights the importance of criminogenic opportunities and parental monitoring for understanding the spatial dynamics of neighbourhood disadvantage on offending.